Geology and Wine 6. Terroir of the Red Mountain Appellation, Central Washington State, U.S.A. - Meinert, Lawrence; Busacca, Alan (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2002)
Summary Red Mountain is the newest of five appellations in Washington State and like the majority of Washington vineyards its terroir is influenced by I) the rain shadow effect and volcanic tephra of the Cascade Mountain Range, 2) soils derived from Quaternaryglacial sediments and wind-blown loess overlying Miocene basalt, and 3) a warm, dryclimate with abundant sunshine and coolnights due to high latitude (N 46e) and topography. Variations of rooting depth, textures, calcium carbonate content, and other properties of vineyard soils are directly influenced by Quaternary glacial flood deposits in the back-eddy of Red Mountain and by the variable nature of the loess and dune cover on the flood deposits. This is the first demonstration of the effect of paleohydrology on vineyard site characteristics. In the past two years, wines made from Red Mountain grapes have received nine scores of > 94 out of 100 in independent blind tastings and merlot wine made from Red Mountain grapes has been ranked as the best in the United States for each of the past two years by two different national wine magazines. Red Mountain is one of the warmest and driest viticultural sites in Washington State, having heat summation (growing degree days) and total sunshine similar to Napa Valley, California which is 1000 km farther south. Other wine regions that havebeen influenced by the worldwide glacial processes that were so important in the development of Washington vineyards include the gravel mounds that underliemost of the first growth vineyards of Graves-Médoc, Bordeaux, France and some of the outwash gravel plains of New Zealand.